Utilization of Moringa Leaf Extract in Processed Products Pudding as an Effort to Prevent Anemia - Febry Mutiariami Dahlan; Armanih; Febriana R; Rizqiyatun A; Yusniar Tito; Ati Herawati; Nurita Y; Septiani H (International Journal of Community Services, 2025)
Objective: This community service was carried out with the aim of overcoming priority problems at the Bekasi City Hospital, namely anemia in pregnant women. Method: The method used in this community service uses lectures, discussions, and demonstrations. The target is pregnant women who experience anemia. Results: The results of this community service, pregnant women understand and comprehend the counseling and complementary therapy "PULOR CEMIA" which can be applied to overcome anemia. Conclusion: Based on the evaluation of the counseling and provision of Moringa Leaf Pudding during community service, the intervention given went well and effectively with the results that pregnant women were able to answer questions and know how to prevent and treat anemia.